Two new Isotomidae species (Collembola: Entomobryomorpha) from Rio de Janeiro State, Brazil - Mendonça, Maria Cleide De; Queiroz, Gabriel Costa (Zootaxa, 2017)
In the present paper, two new species of Isotomidae belonging to the genera Isotomiella Bagnall, 1939 and Paracerura Deharveng & Oliveira, 1994 are described and illustrated. Isotomiella denticulata sp. nov. is distinguished from all known species specially by a single tooth in the inner edge of the unguis, a unique feature among the members of the genus. Paracerura bella sp. nov., differs from other congeners with respect to overall coloration, the sensillary pattern on tergite abd. IV–V and type of chaetae on both lateral margins of dens. Both species are described from Rio de Janeiro, Brazil.